1978
DOI: 10.1002/j.1552-4604.1978.tb01577.x
|View full text |Cite
|
Sign up to set email alerts
|

Cinoxacin: Pharmacokinetics and the Effect of Probenecid

Abstract: Cinoxacin is a new synthetic organic antibacterial compound which has a serum half-life of approximately 1 hour. Most of the drug is eliminated in man by the kidney, primarily as unchanged drug. The renal clearance of cinoxacin is slightly greater than the usually accepted value for the average glomerular filtration rate, which suggests that it is probably filtered and is also secreted by the tubule. Results after pretreatment with probenecid further suggest secretion of the drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

1982
1982
1996
1996

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…Serum and urinary levels, as well as pharmacokinetic parameters of Cinoxacin determined in this study are in agreement with the data reported in the literature (1,2,3, 6,7,13,15,20). For pipemidic acid however we have found a larger percentage of urinary recovery (83% over 24 h) than cited by Humbert et al (12) (63% over 24 h) or Soussy et al (22) (48.3% over 24 h).…”
Section: Discussionsupporting
confidence: 82%
“…Serum and urinary levels, as well as pharmacokinetic parameters of Cinoxacin determined in this study are in agreement with the data reported in the literature (1,2,3, 6,7,13,15,20). For pipemidic acid however we have found a larger percentage of urinary recovery (83% over 24 h) than cited by Humbert et al (12) (63% over 24 h) or Soussy et al (22) (48.3% over 24 h).…”
Section: Discussionsupporting
confidence: 82%
“…In humans, AM-715 is eliminated predominantly by renal excretion and is metabolized only to a small extent (13). Little is known, however, of the mechanisms by which AM-715 is excreted and, specifically, whether it is actively secreted by the renal tubules in a fashion similar to that of such organic acids as nalidixic acid (7), piromidic acid (7), pipemidic acid (10), miloxacin (7), or cinoxacin (8,14). The purpose of the present study was to examine the mechanism of renal excretion of AM-715 in rabbits, dogs, and humans.…”
mentioning
confidence: 99%
“…Tubular secretion has been observed with nalidixic acid (10), piromidic acid (10), miloxacin (10), and norfloxacin (22) in rabbits; pipemidic acid (12) in dogs; and cinoxacin (11,20), norfloxacin (22), and ciprofloxacin (25) in humans.…”
Section: Discussionmentioning
confidence: 99%